Activating children through exergaming – A case study - Sillsten, Samuli (My University, 2024)
This thesis examines exergaming as a possibility to increase activity in children. Aim of this thesis is to research exergaming and motivational ways used in exergaming and based on the research to design and implement good gamified application that encourages children to be more active. The thesis focuses first on theory of gamification and motivational ways on gamification. After that the thesis focuses more specifically on exergaming and motivation in exergaming. Thesis also goes through some previous studies on the subject. After theory part we go through the design and implementation phases of the gamified application. We also introduce the platform to which the application was implemented on, interactive ball Pall0. With the designed and implemented application there is two test sessions with children held where we gather information for the empirical research through questionnaire survey. Based on previous studies and the results on this study exergaming can be used to increase activity within children as long as the exergame is well designed and implemented.
Keywords: gamification, exercise, exergame, children